Studies on performance of standard and non-standard configuration of Franklin Air terminals - Ong, Lai Mun (2006)
Buildings installed with 200-year-old Franklin rods were reportedly damaged when struck by lightning. When intercepted by lightning, air terminals may also be damaged or physically changed in its tip configurations. In such cases, it is crucial to determine whether the damaged lightning air terminal can still perform as an effective lightning protection system. This research aims to investigate the performance of different tip configuration of air terminals after being struck by lightning. Six different rod tip configurations-sharp, blunt, standard, concave, flat and conical shape rod tip were tested in the laboratory. Two stages of tests were carried out. The first stage of tests was carried out under the application of impulse voltages only and without the pre-ionization condition to simulate the approach of a downward leader. The second stage involved the application of DC and UV radiations to ionize the tip prior to applying impulse voltages. In both conditions, two sets of individual tests and competitive tests were carried out for all air terminals. The individual test is for obtaining the breakdown voltage and the timeto- breakdown. The number of strikes per air terminal were recorded when pairs of air terminals were subjected to competitive tests. During competitive tests in preionization condition, corona was observed at the tips. The flat and concave rods were found to have high formation of corona which results in higher breakdown voltage. The result also shows that the blunt rod is the best performance rod over the others, having the most consistent breakdown voltage and time-to-breakdown in both non-ionized and pre-ionized tips. It is learnt that pre-ionization condition should be adopted when testing air terminals in laboratory to obtain more reliable results as it is able to simulate the condition almost similar to the real lightning condition.